Global Trends, Gaps, and Methodological Insights: Intercultural Research in Indonesian Applied Linguistics and Language Education - Artanti, Yeni; Azhari, Azhari (Journal of Ethnic and Cultural Studies, 2025)
Intercultural competence has become increasingly vital in multilingual, multicultural societies, especially in schools where language is used to resolve cultural differences. In Indonesia, a country with more than 700 languages and 1,300 ethnic groups, applied linguistics has enormous potential to promote inclusive and culturally responsive education. However, the state of intercultural research in Indonesian applied linguistics remains fragmented, thematically limited, and methodologically constrained. This study performed a mixed-methods systematic literature review (SLR) of 93 peer-reviewed publications from 2000 to 2024, utilizing the PRISMA framework as a guide. The results show that research output has risen sharply since 2019, but the field is mostly made up of qualitative methods and lacks experimental or longitudinal designs. The majority of published research concentrates on foreign language education, with scant emphasis on curriculum development, educator perspectives, or policy integration. Researchers rarely use established models, like Intercultural Communicative Competence and Deardorff’s Process Model, and they seldom utilize advanced analytical methods. These gaps highlight the necessity for methodological diversification, theoretical integration, and expansive thematic investigation. By linking global frameworks to the Indonesian context, this study enhances international dialogue on intercultural education and provides strategic guidance for forthcoming research, policy formulation, and pedagogical advancement.